2016
DOI: 10.1073/pnas.1606862113
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic MELK-eIF4B signaling controls protein synthesis and tumor cell survival

Abstract: The protein kinase maternal and embryonic leucine zipper kinase (MELK) is critical for mitotic progression of cancer cells; however, its mechanisms of action remain largely unknown. By combined approaches of immunoprecipitation/mass spectrometry and peptide library profiling, we identified the eukaryotic translation initiation factor 4B (eIF4B) as a MELK-interacting protein during mitosis and a bona fide substrate of MELK. MELK phosphorylates eIF4B at Ser406, a modification found to be most robust in the mitot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 37 publications
5
58
2
Order By: Relevance
“…4,5 Maternal embryonic leucine zipper kinase (MELK) is a member of the AMP protein kinase (AMPK) family of serine/threonine kinases, and MELK activates multiple cellular pathways that drive oncogenic growth. [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL). [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Maternal embryonic leucine zipper kinase (MELK) is a member of the AMP protein kinase (AMPK) family of serine/threonine kinases, and MELK activates multiple cellular pathways that drive oncogenic growth. [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL). [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL).…”
Section: Introductionmentioning
confidence: 99%
“…The ATM-CHK2 pathway is activated when DSBs occur. MELK was proven to be associated with mitotic progression and DNA damage [8][9][10][11][12][13]. Kig et al confirmed that MELK was required for the repair of DNA damage (including dou-…”
mentioning
confidence: 99%
“…It is possible that certain oncogenic pathways generate specific, druggable vulnerabilities in mitosis, although none has yet been found. Recent work suggested MELK kinase activity is required for successful mitosis in certain breast cancer lines, but not others [90, 91]. Whether MELK is a useful target remains to be seen, but this work is encouraging in the context that it is at least theoretically possible to perturb mitosis selectively in some cancer genotypes.…”
Section: Implications For Improving Anti-mitotic Therapymentioning
confidence: 84%
“…MELK is highly overexpressed in several cancer types and its inhibition has been shown to block the tumor growth of some cancers (Inoue et al, 2016; Joshi et al, 2013; Kato et al, 2016; Wang et al, 2016; Wang et al, 2014). Interestingly, MELK knockout mice are viable and do not show any specific phenotypes (Wang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%